Pemanfaatan Facebook dan WhatsApp Sebagai Sarana Promosi - Jajang Suherman; Armansyah M. Sarusu; Ricky Rohmanto; Amalia Faroha (Ma'soem University, 2026)
This community service activity aims to improve digital marketing skills at Warung Bunda Afifah Catering in Rancaekek, Bandung through the use of Facebook and WhatsApp social media as promotion tools. The method used is a participatory method with a training and mentoring approach, which includes stages of problem identification, digital promotion strategy planning, implementation of training on the use of Facebook and WhatsApp Business, as well as evaluation of activity results. Data collection techniques were carried out through observation, interviews, and documentation before and after the activities took place. The results of the activities showed an increase in partners' understanding and skills in managing Facebook and WhatsApp accounts as promotional media, including in creating engaging content, managing product catalogs, and communicating with customers. In addition, there was an increase in promotional reach and interaction with consumers, which impacted the growth in the number of orders. Thus, the use of Facebook and WhatsApp has been proven effective as a simple, inexpensive, and easy-to-implement digital marketing strategy for small businesses such as Catering Warung Bunda Afifah.